2003
DOI: 10.1177/009164710303100403
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among Dutch Reformed Pastors

Abstract: The present study examined the degree of burnout among Dutch reformed pastors and aspects that may be conducive to the onset of burnout. They were asked to report how difficult they found their tasks and what options they had to alleviate the pressure of work they experienced. Compared with other human service professionals the results show that pastors have relatively high scores on emotional exhaustion and relatively low scores on depersonalization. Pastors have relatively low scores on personal accomplishme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 15 publications
2
46
0
2
Order By: Relevance
“…An example item on this dimension is 'I feel I'm positively influencing other people's lives through my work. ' The model of burnout proposed by Maslach and Jackson (1986) and operationalized through the Maslach Burnout Inventory has been used (in its original form) in a series of studies among clergy, including those reported by Warner and Carter (1984), Strümpfer and Bands (1996), Rodgerson and Piedmont (1998), Stanton-Rich and Iso-Ahola (1998), Virginia (1998), Evers and Tomic (2003), Golden, Piedmont, Ciarrocchi, andRodgerson (2004), Raj andDean (2005), Miner (2007aMiner ( , 2007b, Doolittle (2007), Buys and Rothmann (2010), Joseph, Corveleyn, Luyten, and de Witte (2010), Parker andMartin (2011), Joseph, Luyten, Corveleyn, andde Witte (2011) and Küçüksüleymanoğlu (2013). The Maslach Burnout Inventory has also been specifically modified for use among clergy and employed in a series of studies, including those reported by Francis and Rutledge (2000), Francis, Louden, and Rutledge (2004), Francis andTurton (2004a, 2004b), Randall (2004Randall ( , 2007Randall ( , 2013, Rutledge and Francis (2004), Rutledge (2006), Francis, Turton, and Louden (2007), and Turton and Francis (2007).…”
Section: Conceptualisation and Measurement Of Work-related Psychologimentioning
confidence: 99%
“…An example item on this dimension is 'I feel I'm positively influencing other people's lives through my work. ' The model of burnout proposed by Maslach and Jackson (1986) and operationalized through the Maslach Burnout Inventory has been used (in its original form) in a series of studies among clergy, including those reported by Warner and Carter (1984), Strümpfer and Bands (1996), Rodgerson and Piedmont (1998), Stanton-Rich and Iso-Ahola (1998), Virginia (1998), Evers and Tomic (2003), Golden, Piedmont, Ciarrocchi, andRodgerson (2004), Raj andDean (2005), Miner (2007aMiner ( , 2007b, Doolittle (2007), Buys and Rothmann (2010), Joseph, Corveleyn, Luyten, and de Witte (2010), Parker andMartin (2011), Joseph, Luyten, Corveleyn, andde Witte (2011) and Küçüksüleymanoğlu (2013). The Maslach Burnout Inventory has also been specifically modified for use among clergy and employed in a series of studies, including those reported by Francis and Rutledge (2000), Francis, Louden, and Rutledge (2004), Francis andTurton (2004a, 2004b), Randall (2004Randall ( , 2007Randall ( , 2013, Rutledge and Francis (2004), Rutledge (2006), Francis, Turton, and Louden (2007), and Turton and Francis (2007).…”
Section: Conceptualisation and Measurement Of Work-related Psychologimentioning
confidence: 99%
“…The Maslach Burnout Inventory has been used in its original form among clergy by a number of studies, including Warner and Carter (1984), Strümpfer and Bands (1996), Rodgerson and Piedmont (1998), Stanon-Rich and Iso-Ahola (1998), Virginia (1998), Evers and Tomic (2003), Golden, Piedmont, Ciarrocchi, and Rodgerson (2004), Raj and Dean (2005), Miner (2007aMiner ( , 2007b, and Doolittle (2007). When Rutledge and Francis (2004) tested the Maslach Burnout Inventory among clergy in the United Kindgom, they discovered that some of the items failed to reflect the situation, culture and vocabulary that clergy recognised to describe their situation.…”
Section: Maslach Burnout Inventorymentioning
confidence: 99%
“…These studies included work reported by Warner and Carter (1984), Strümpfer and Bands (1996), Rodgerson and Piedmont (1998), Stanton-Rich and Iso-Ahola (1998), Virginia (1998), Evers and Tomic (2003), Golden, Piedmont, Ciarrocchi, and Rodgerson (2004), Raj and Dean (2005), Miner (2007a, 2007b and Doolittle (2007).…”
Section: Between Two Worlds: Understanding and Managing Clergy Stressmentioning
confidence: 99%